Occurrence, extension, and severity of gingival margin alterations after orthodontic treatment. - Closs, Luciane Q; Grehs, Betina; Raveli, Dirceu Barnabé [UNESP]; Rösing, Cassiano Kuschenbecker (My University, 2008)
To assess the occurrence, extension, and severity of gingival margin alterations in a sample of youth after orthodontic treatment. Records from 209 Caucasian adolescents (118 female and 91 male) before and after orthodontic treatment were selected. Patients presented a mean age at the beginning of orthodontic treatment of 11.20 ± 1.86 years and a final mean age of 14.72 ± 1.83 years. Class I and II patients with mandibular incisors and canines that were completely erupted and with spacing or crowding not exceeding 4 mm were evaluated. The presence of gingival recession on the labial surface of the mandibular anterior teeth was evaluated in intraoral photographs and casts made before and after treatment. The proportion of patients with gingival recession after treatment was statistically higher than at the beginning (P<.001). After orthodontic treatment, gingival recession was not present in any of the teeth for 63.6% of the patients; in 29.2% of the patients, recession was present in at least 1 tooth. In terms of severity, the majority of affected teeth (47%) presented gingival recession less than 2 mm and in 2% more than 4 mm. It may be concluded that alterations in the gingival margin, especially gingival recession, occur in patients after orthodontic therapy, but the extent and severity of this finding are low. COPYRIGHT © 2007 BY QUINTESSENCE PUBLISHING CO, INC.
Keywords: adolescent; canine tooth; child; classification; dental procedure; female; follow up; gingiva disease; human; incisor; instrumentation; male; malocclusion; mandible; medical photography; orthodontic device; pathology; periodontal disease; Adolescent; Child; Cuspid; Dental Models; Female; Follow-Up Studies; Gingival Recession; Humans; Incisor; Male; Malocclusion, Angle Class I; Malocclusion, Angle Class II; Mandible; Orthodontic Brackets; Orthodontic Wires; Photography, Dental; Tooth Movement